Promoting quality of life: impact evaluation of the program “Strength for a healthy life” (2009)
In the female population, depression and anxiety are two of the most common health problems. In addition, worry, irritability and fatigue are symptoms by which women commonly seek consultation at health centers. If to this scenario we add living in poverty, the situation is intensified. This is why we see with more frequent studies that show the difference between men and women when they experience these kind of situations. This study aims at observing the relationship between quality of life, poverty, and the Program: Strength for a Healthy Life (PSFHL). This program promotes the development of cognitive and emotional capacities to strengthen the lives of low-income women (the average household income is of $444.00 dollars). The impact evaluation is descriptive, with a non-experimental and longitudinal design. Results show that the PSFHL has a significant impact that prevails through time, that women increase their quality of life, and that they decrease their symptoms.